Pengujian Sistem Informasi Point Of Sale Berbasis Website Menggunakan Metode Waterfall pada CV Tray Store - Tri Mulyani; Hafidh Zalainus Sahrul Ausath; Sandra Putri Saigon; Ferdiansah; Aries Saifudin (CV. Multi Kreasi Media, 2023)
At the CV Tray shop, the system is still based on a manual recording system which is less effective because it can cause data to be lost frequently and makes it difficult to find sales reports and stock items. However, current technological advances are very helpful in data processing in various fields. In this study, we propose creating a POS (Point of Sale) application to overcome existing problems and ensure smooth store operations. The method used is the waterfall method. The software is developed by going through several stages of needs analysis, design, program writing, and testing sequentially. This application that has been created and has been tested can facilitate recording, counting, and ordering at the CV Tray store. The programming languages used in this system are PHP, MYSQL, and CODEIGNITER.